If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -4t = 6t + -22 Reorder the terms: 8 + -4t = -22 + 6t Solving 8 + -4t = -22 + 6t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-6t' to each side of the equation. 8 + -4t + -6t = -22 + 6t + -6t Combine like terms: -4t + -6t = -10t 8 + -10t = -22 + 6t + -6t Combine like terms: 6t + -6t = 0 8 + -10t = -22 + 0 8 + -10t = -22 Add '-8' to each side of the equation. 8 + -8 + -10t = -22 + -8 Combine like terms: 8 + -8 = 0 0 + -10t = -22 + -8 -10t = -22 + -8 Combine like terms: -22 + -8 = -30 -10t = -30 Divide each side by '-10'. t = 3 Simplifying t = 3
| 7x+4=24 | | 15s-8c=5c+48 | | 15X-19+4X+53-8X=2X-43+86+9X+35+-X | | 3m+24=7m | | -1/2m+8=10 | | 68=-2(m+5)+m | | (3x-8)(x+1)=0 | | 3z+24=-7z | | 5=5(x-4)+5-4x | | 4q+2=4 | | 68=-2 | | 1/7(x+2)=4 | | 0.4(0.71+6x)=3.2x | | a/15=b | | let(f)=5x^2-8x+3 | | 8X+59-5X=X-84+242+X | | 8+6+2x=8x | | 4t-2=1 | | x+2=4(4x-3) | | 2x=4-6 | | 3/4(x-16)=-51/4 | | 8p+8=3p-2 | | 6(c-9)=-30 | | 1x+3x+4=4x | | 5X-74+8X=7X+148+5X | | -13-9y=13 | | 4x^2-8x+6=0 | | 3n-11=4 | | 8q^2-10+3=0 | | 7+1=m | | 8p-11=-2p+7 | | y=3r-5y |